Praktik “Jurnalisme Syariah” di Radio MQ FM Yogyakarta - Abdul Rohman (Jurnal Komunikasi, 2007)
Syariah principle that is happening now bears a new phenomenon, not only in financial field but also in media. Radio as one of mass media does not want to leave behind. One of radio that is based on syariah principle is Radio MQ FM Yogyakarta. In its operations, Radio MQ FM Yogyakarta creates news as the significant power. As a syariah radio, Radio MQ FM Yogyakarta's newsroom finds, collects, and delivers news by internalizing its own principle. The principle is BALM, abbreviationfrom Benar (Truth), Akurat (Accuracy), Lengkap (Completeness), and Manfaat (Useful). By using observation method, this research tries to describe all kinds of Radio MQFM Yogyakarta newsroom activities.